Speech Effort Measurement and Stuttering: Investigating the Chorus Reading Effect. - Ingham, Roger J.; Warner, Allison; Byrd, Anne (Journal of Speech, Language & Hearing Research, 2006)
Purpose: The purpose of this study was to investigate chorus reading's (CR's) effect on speech effort during oral reading by adult stuttering speakers and control participants. The effect of a speech effort measurement highlighting strategy was also investigated. Method: Twelve persistent stuttering (PS) adults and 12 normally fluent control participants completed 1-min base rate readings (BR—nonchorus) and CRs within a BR/CR/BR/CR/BR experimental design. Participants self-rated speech effort using a 9-point scale after each reading trial. Stuttering frequency, speech rate, and speech naturalness measures were also obtained. Instructions highlighting speech effort ratings during BR and CR phases were introduced after the first CR. Results: CR improved speech effort ratings for the PS group, but the control group showed a reverse trend. Both groups' effort ratings were not significantly different during CR phases but were significantly poorer than the control group's effort ratings during BR phases. The highlighting strategy did not significantly change effort ratings. Conclusion: The findings show that CR will produce not only stutter-free and natural sounding speech but also reliable reductions in speech effort. However, these reductions do not reach effort levels equivalent to those achieved by normally fluent speakers, thereby conditioning its use as a gold standard of achievable normal fluency by PS speakers. Reprinted by permission of the publisher.